New trends in image analysis and processing - ICIAP 2019 : ICIAP international workshops, BioFor, PatReCH, e-BADLE, DeepRetail, and Industrial Session, Trento, Italy, September 9-10, 2019 : revised selected papers /: ICIAP international workshops, BioFor, PatReCH, e-BADLE, DeepRetail, and Industrial Session, Trento, Italy, September 9-10, 2019 : revised selected papers. ([2019]) - Unknown
No abstract available